2019
DOI: 10.1111/cyt.12696
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of breast fine needle aspiration cytology interpretation with subsequent surgical pathology: An 18‐year review from a single sub‐Saharan African institution

Abstract: Introduction:There are many merits to fine needle aspiration cytology (FNAC) in evaluation of palpable breast lesions. We set out to determine the concordance of breast FNAC interpretation with subsequent surgical pathology in the resource-limited healthcare setting of rural Kenya.Methods: African Inland Church Kijabe Hospital electronic pathology files were retrospectively reviewed from 1/1999-9/2017. All breast FNAC cases and subsequent surgical pathology specimens were identified. FNAC interpretations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…Even then, the ROM of the atypical, suspicious of malignancy and malignant cytological categories in our study is compatible with the expected ROM of the IAC Yokohama system 14,15 . The diagnostic accuracy of breast FNAB by the IAC Yokohama system in the present study is similar to previous reported studies when the latter are re‐analyzed 15‐18 (Table 5), with the high AUC reported in the studies confirming the high diagnostic accuracy of breast FNAB.…”
Section: Discussionsupporting
confidence: 91%
“…Even then, the ROM of the atypical, suspicious of malignancy and malignant cytological categories in our study is compatible with the expected ROM of the IAC Yokohama system 14,15 . The diagnostic accuracy of breast FNAB by the IAC Yokohama system in the present study is similar to previous reported studies when the latter are re‐analyzed 15‐18 (Table 5), with the high AUC reported in the studies confirming the high diagnostic accuracy of breast FNAB.…”
Section: Discussionsupporting
confidence: 91%
“…The IAC Yokohama System has defined minimum criteria for adequacy and recommends the inadequate rates (category I) be less than 5%. Category I in published studies ranges from 5.7% to 40% 9‐14 . Our study reports a higher percentage of inadequate aspirates (9%) than that recommended by IAC, despite being comparable to other recently published Indian and Western studies 9‐14 …”
Section: Discussionsupporting
confidence: 82%
“…Category I in published studies ranges from 5.7% to 40% 9‐14 . Our study reports a higher percentage of inadequate aspirates (9%) than that recommended by IAC, despite being comparable to other recently published Indian and Western studies 9‐14 …”
Section: Discussionsupporting
confidence: 82%
“…McHugh et al . [ 12 ] observed highest sensitivity and specificity in similar scenarios, but they observed maximum accuracy when only malignant cases were considered as positive test results [ Table 5 ].…”
Section: Discussionmentioning
confidence: 99%